Medical and Sociodemographic Factors Associated with Human Papillomavirus (HPV) Vaccination Adherence among Female Survivors of Childhood Cancer - Klosky, James L. (Pediatr Blood Cancer, 2015)
BACKGROUND: Among those 9-26 years of age, vaccination can prevent specific types of genital human papillomavirus (HPV), the most common sexually transmitted infection and cause of cervical and other cancers. The objective of this study was to estimate the prevalence of and factors associated with HPV vaccine initiation and completion among females surviving childhood cancer. PROCEDURE: One-hundred fourteen young adults and 230 mothers with daughters surviving childhood cancer completed surveys querying HPV vaccination history along with medical and sociodemographic factors potentially associated with vaccination outcomes. Vaccination rate differences by age necessitated analysis of outcomes by age group: 9-13 years (preadolescents), 14-17 years (adolescents), and 18-26 years (young adults). Multivariable logistic regression was utilized to identify factors associated with HPV vaccination outcomes. RESULTS: Overall, 34.6% (119/344) of survivors initiated and 20.9% (72/344) completed HPV vaccination. Preadolescents were least likely to have initiated vaccination (P<0.001). Physician recommendation was associated with initiation across age groups (OR=6.81–11.96, Ps<0.001-.01), whereas older age at diagnosis (≥12 years of age) was associated with lower vaccination initiation among young adults only (OR=0.28; 95% CI, 0.10–0.76, P=0.012). Physician recommendation (OR=7.54; 95% CI, 1.19–47.69, P=0.032; adolescent group) and greater treatment intensity (OR=5.25; 95% CI, 1.00–27.61, P=0.050; young adult group) were associated with vaccine completion, whereas being non-White was associated with decreased vaccination completion (OR=0.17; 95% CI, 0.05–0.66, P=0.010; adolescent group). CONCLUSIONS: A minority of youths surviving childhood cancer have initiated or completed HPV vaccination. Strategies to increase vaccination among survivors are discussed.